Higher medical training in venereology. Issue 2 (April 1982) - Schofield, C B
Abstract : In a review of the organisation of higher medical training in Britain leading to accreditation for those intending to specialize in venereology within the National Health Service suggestions are made for improving the present system. These include the enrollment of trainees in general medicine as well as in venereology to ensure a broad general experience of medicine. The establishment of an agreed curriculum in venereology for trainees is thought desirable. Improvement in undergraduate education in venereology is necessary if recruitment of trainees to the specialty is to be increased. The diploma courses in venereology are mainly attended by foreign graduates; the numbers are likely to be reduced by the recent heavy increases in fees. Although adequate practical experience of the tropical venereal diseases cannot be provided, these courses give a good general experience of venereology as ideally practised, much of which is relevant to the conditions under which the overseas trainees will have to work on return to their own countries. Secondment of our own trainees work in centres in developing countries as an approved part of their training would benefit both them and their hosts.